2022
DOI: 10.3390/nu14020291
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Maternal Vitamin D Status and Socio-Economic Status on the Risk of Spontaneous Abortion: Evidence from Henan Province, China

Abstract: Background: Maternal vitamin D deficiency might generate adverse reproductive outcomes, and socio-economic inequalities in micronutrient-related diseases have often been found. This study aimed to explore the interactive effects of maternal vitamin D status and socio-economic status (SES) on risk of spontaneous abortion. Methods: A population-based case–control study was conducted including 293 women with spontaneous abortion and 498 control women in December 2009 and January, 2010 in Henan Province, China. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…The abundance of disparities including medical racism, food insecurity, and other race‐related SDOH are known to severely affect birth outcomes in Black women 23,24,45,46 . Outside of the United States, SES was correlated with vitamin D deficiency and increased risk for negative birth outcomes in a study on women from the Henan Province in China 48 . These data demonstrate how SDOH, including race/ethnicity and SES, undeniably recombine with vitamin D status to alter public health.…”
Section: Public Health Perspectives On the Vitamin D Theorymentioning
confidence: 78%
See 1 more Smart Citation
“…The abundance of disparities including medical racism, food insecurity, and other race‐related SDOH are known to severely affect birth outcomes in Black women 23,24,45,46 . Outside of the United States, SES was correlated with vitamin D deficiency and increased risk for negative birth outcomes in a study on women from the Henan Province in China 48 . These data demonstrate how SDOH, including race/ethnicity and SES, undeniably recombine with vitamin D status to alter public health.…”
Section: Public Health Perspectives On the Vitamin D Theorymentioning
confidence: 78%
“…23,24,45,46 Outside of the United States, SES was correlated with vitamin D deficiency and increased risk for negative birth outcomes in a study on women from the Henan Province in China. 48 These data demonstrate how SDOH, including race/ ethnicity and SES, undeniably recombine with vitamin D status to alter public health. Observations from these studies underscore the importance of including cultural factors in future research interpreting the effect of vitamin D deficiencies on reproductive health and fitness.…”
Section: Racial Health Disparities and Vitamin D Deficienciesmentioning
confidence: 86%
“…Although the observational findings suggested an association, a causal relationship between serum 25OHD concentration, vitamin D deficiency, and miscarriage was not supported by our MR analysis. This discrepancy could be attributed to confounding factors or biases inherent in observational studies, such as maternal age, BMI, smoking and alcohol history, socioeconomic status, chronic diseases, sampling season, and other unknown confounders, which are minimized in MR analysis ( Veleva et al , 2008 ; Pereira-Santos et al , 2015 ; Pourshahidi, 2015 ; Quenby et al , 2021 ; Lin et al , 2022a , 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research found that having a lower socioeconomic status is the risk factor for VD deficiency in women of reproductive age and having a maternal low socioeconomic status may even strengthen the risk of VD deficiency, resulting in spontaneous miscarriage [ 30 ]. The important findings in this study were that the interactions between passive smoking and not taking nutrition supplementation (OR 3.40, 95% CI 2.26–5.13), passive smoking and insufficiently consuming eggs (OR 2.87, 95% CI 2.20–4.10), and passive smoking and insufficiently consuming milk dairy products (OR 2.18, 95% CI 1.33–3.58) were all associated with an increased risk of VD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the Birth Defects Monitoring and Comprehensive Intervention Project, from December 2009 to February 2010, a population-based study was performed in Henan Province, China; this design has been published previously [ 29 , 30 ]. In brief, the project obtained a representative sample of married, non-pregnant women in Henan Province through multistage cluster sampling methods.…”
Section: Methodsmentioning
confidence: 99%